1967
DOI: 10.2134/agronj1967.00021962005900030013x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride on Phosphorus Uptake by Corn Roots1

Abstract: A study was made on the effect of KCl on P uptake by 20‐day‐old corn seedlings grown in water culture and 4‐day‐old excised corn roots grown on 0.2 mM CaSO4 solution. All P solutions were adjusted to pH 4. Those used for excised roots contained 0.2 mM CaSO4 and those used for 20‐day‐old corn seedlings contained 1.2 mM KNO3, 0.8 mM Ca(NO3)2, and 0.4 mM MgSO4. One‐hour absorption periods using concentrations up to 0.l M KCl showed no effect on 32P uptake from 2 to 260 µM KH2PO4 solutions with either type of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Moreover, in recent experiments the apparent affinities for K + uptake by different barley cultivars were closely correlated with growth rates under K + limited conditions (Glass and Perley, 1980). 7.6) is similar to that found for cereal roots (Carter and Lathwell, 1967). grow in PO~depleted soils, Cook (1973) found no evidence that roots of A. vesicaria or A. conduplicata had unusually high affinity for this nutrient.…”
Section: Ion Absorption and Concentrationsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, in recent experiments the apparent affinities for K + uptake by different barley cultivars were closely correlated with growth rates under K + limited conditions (Glass and Perley, 1980). 7.6) is similar to that found for cereal roots (Carter and Lathwell, 1967). grow in PO~depleted soils, Cook (1973) found no evidence that roots of A. vesicaria or A. conduplicata had unusually high affinity for this nutrient.…”
Section: Ion Absorption and Concentrationsupporting
confidence: 61%
“…There is no indication in Fig.7.6 that the ability of A triplex leaves to absorb CI-to much higher concentrations than in Citrus leaves is determined by the relationship between rate of ion uptake and external solution concentration. For example, K + absorption from solutions of low concentrations is insensitive to high levels of Na + (Epstein, 1972) and por uptake is insensitive to Cl- (Carter and Lathwell, 1967). Uptake versus concentration experiments also show that ion uptake by roots may be quite specific and insensitive to high concentrations of other ions.…”
Section: Ion Absorption and Concentrationmentioning
confidence: 99%
“…Chlorine level in the substrate has been shown to decrease P concentration or content in range grasses (Gausman et al, 1954) depending on species, but to have little effect on P content of potato (Solanum tuberosum L.) (Gausman et al, 1958). Carter and Lathwell (1967) found no effect on Cl on P uptake in corn (Zea mays L.), however, they maintained a solution pH of 4, which can be considered artificially low in relation to many field soils and non-optimum for P uptake (Tisdale and Nelson, 1970). Carter and Lathwell (1967) quoted studies with rice (Oryza sativa L.) which showed an effect of Cl on P uptake at low but not high substrate P levels.…”
mentioning
confidence: 99%
“…Carter and Lathwell (1967) found no effect on Cl on P uptake in corn (Zea mays L.), however, they maintained a solution pH of 4, which can be considered artificially low in relation to many field soils and non-optimum for P uptake (Tisdale and Nelson, 1970). Carter and Lathwell (1967) quoted studies with rice (Oryza sativa L.) which showed an effect of Cl on P uptake at low but not high substrate P levels. Chabra et al (1976) found a plateau response in P uptake at levels of solution chloride above approximately 150 ~-tM for tomato (Lycopersicum esculentum Mill).…”
mentioning
confidence: 99%